ULTRASTUCTURAL AND FUNCTIONAL MORPHOLOGY OF EGGSHELLS SUPPORTS THE IDEA THAT DINOSAUR EGGS WERE INCUBATED BURRIED IN A SUBSTRATE - Deeming D.C. (My University, 2006)
The reproductive biology of dinosaurs is of great interest, particularly in light of the many fossil eggs assigned to this group. The ultrastructural characteristics of dinosaur eggshells are examined in order to calculate water vapour conductance, which indicates the nesting environment. Data were mainly derived from the literature but new values are also presented. Allometric analyses were carried out on a variety of shell parameters against predicted egg mass, and comparison was made with allometric equations for bird eggs. Shell thickness was generally larger than seen for extant birds. Total pore number and pores per unit area were similar to values predicted from bird eggs. Total pore area showed an isometric increase with egg mass, parallel to the relationship for birds, but the constant value was an order to magnitude higher than the bird values. Pore radius was unaffected by egg mass. Water vapour conductance showed an allometric increase with egg mass, parallel to the bird values, but for any given egg mass values for dinosaurs were an order of magnitude higher. Mass-specific water vapour conductance was unaffected by egg mass but was an order of magnitude higher than the bird values. Water vapour conductance per pore showed an allometric decrease with egg mass but again the predicted values were an order of magnitude higher than for bird eggs. The ultrastructural characteristics of dinosaur eggshells indicate that the nesting environment had to be saturated with water vapour and that dinosaur eggs had to be fully buried in a substrate. In this sense, therefore, dinosaur eggs resemble more those of modern reptiles than those of birds. As a consequence, maintenance of incubation conditions would have depended on the prevailing environment. © 2006 The Palaeontological Association.
Keywords: DINOSAUR; EGGSHELLS; NESTING ENVIRONMENT; PORE; ULTRASTRUCTURE; WATER VAPOUR CONDUCTANCE